PENGGUNAAN MEDIA POP UP BOOK DALAM MELATIH KETERAMPILAN BERDISKUSI SISWA PADA MATA PELAJARAN IPAS MATERI EKOSISTEM DI KELAS V SD NEGERI 5 SONGAN BANGLI - Sridiana, Ni Nyoman; Arini, Ni Wayan; Suryawan, I Gde (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of using innovative learning media to create active, interactive, and student-centered learning. In science and social studies (IPAS) learning at the elementary school level, the learning process is still dominated by conventional methods, causing student participation and discussion skills to develop less optimally. In addition, ecosystem material, which is abstract in nature, is often difficult for students to understand when delivered only through verbal explanations and textbooks. Therefore, Pop Up Book media is considered an attractive, concrete, and interactive alternative learning medium that can help improve students’ conceptual understanding and discussion skills in IPAS learning. This study aimed to: (1) describe the use of Pop Up Book learning media in ecosystem material for fifth-grade students at SD Negeri 5 Songan, (2) identify the implementation process of Pop Up Book media in classroom learning activities, and (3) determine the impact of using Pop Up Book media on students’ discussion skills and learning activeness. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of the principal, fifth-grade teacher, and fifth-grade students of SD Negeri 5 Songan. Data collection techniques included observation, interviews, and documentation. Data analysis used the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Pop Up Book media involved several stages, including media preparation, introduction and demonstration, group discussions, independent exploration, and learning evaluation. The use of Pop Up Book media positively impacted students’ learning interest, understanding of ecosystem concepts, discussion skills, confidence in expressing opinions, teamwork, and the creation of a more active, interactive, enjoyable, and student-centered learning atmosphere.